A Model for coupled geomechanics and multiphase flow in fractured porous media using embedded meshes. (December 2018) - Ren, Guotong; Jiang, Jiamin; Younis, Rami M.
Abstract: A mixed discretization approach is proposed to accurately and efficiently resolve coupled multiphase flow and geomechanics in fractured porous media. An extended finite element method (XFEM) is applied to approximate the displacement field, and a projection-based embedded-discrete-fracture method (pEDFM) is used to model the multiphase flow. The proposed scheme resolves arbitrary intersections between fractures and the matrix. The proposed discrete fracture treatment allows for embedded meshes where the matrix mesh need not conform to the geometry of the fractures. It is demonstrated that the proposed XFEM-pEDFM scheme is accurate for multiphase flow and geomechanics. Moreover, the computational efficiency and robustness of linear and nonlinear solution methods is assessed. It is demonstrated that the proposed scheme requires specialized solution methods in order to attain favorable computational efficiency.